ANALISIS KEPUASAN PUBLIK ATAS KUALITAS PELAYANAN DI SAT LANTAS POLRES SUKOHARJO - Sudarwati, Istiqomah (GEMA, 2015)
Delivery service in Satlantas Polres Sukoharjo to the community is an application of the function of state officers and as civil servant as well. To create homogeneity of patterns and steps in public service, it needs a general foundation in the form of guidelines which call attention in operational procedure of public service that is given by both the central government and regional government.The research aims at knowing the significant influence between service quality and public satisfaction, and also knowing the gap between reality and expectation. To know how to measure the quality of these services is by analyzing service quality dimension which covers reliability, responsiveness, assurance, empathy and tangibles.The method of the research is survey; to analyze quality service in Satlantas Polres Sukoharjo. Technique of data collection is giving questionnaire to the respondents. Â Sampling is taken by purposive random sampling. There are 100 samples in this research. Â Technique of data analysis is by using hypotheses multiple regression analysis, t test, F test and test by two different mean using SPSS.The result of this research is that there is a significant effect between the following variables; reliability (X1), responsiveness (X2), assurance (X3), empathy (X4), and tangibles (X5) affected public satisfaction. While partially, there is no significant effect between reliability (X1) to satisfaction (Y) and between empathy (X4) to satisfaction (Y). But there is a very significant influence among responsiveness (X2) to satisfaction (Y), between assurance (X3) to satisfaction (Y) and between tangibles (X5) to satisfaction (Y). From five dimensions, there is negative gap between expectation and performance and the average value of the gap is also negative. That mean, public expectation is greater than the performance of quality service during this whole time.